The minimalist home : a room-by-room guide to a decluttered, refocused life - Becker, Joshua; Stanford, Eric (WaterBrook, 2018)
The popular blogger outlines practical guidelines for simplifying a home lifestyle and rendering spaces both peaceful and purposeful while addressing the underlying issues that contribute to home clutter problems.